Physical activity and body image in physiotherapy students - Santos, Paula Clara (2019)
There is a decrease in the physical activity of future physiotherapists, due to readjustments after admission to college. The high levels of sedentarism, cause diverse physical consequences, especially in terms of corporal image perception. This fact is due to a multidimensional construction of several psychosocial factors, which include motivational factors and behavioural changes.